Development of Canva-Based Mathematics Learning Media on the Simple Fractions Concepts - Aeni, Wulan Nur (Jurnal Pendidikan Indonesia Gemilang, 2024)
This research aimed to develop a Canva quiz-based mathematics learning media tested on simple fraction material in grade III elementary schools. The type of research used is Research and Development (RD) research, using learning material instruments, tests, and 4D development models (Define, Design, Development, and Disseminate). Based on the analysis results, including media expert validation, material expert validation, and user validation, it can be concluded that the development of Canva quiz-based media can improve the learning process. This is taken from the results of media validation, obtained good qualifications with an average score of 95.5% (valid), and has material aspects on mathematics problems received good qualifications with an average score of 88%. In the questionnaire results, teachers obtained good qualifications with an average 92% (valid) score. Therefore, the development of canva quiz-based learning media can be used to improve the mathematics learning process in grade III elementary schools.